1991
DOI: 10.1103/physrevc.44.r1725
|View full text |Cite
|
Sign up to set email alerts
|

Total cross section forp+pp+p+π0near threshold

Abstract: We compare a phenomenology of n" production in p-p scattering with recent Indiana University Cyclotron Facility data for energies near threshold. The computed magnitude of the cross section is too small by a factor of about 5, even though the energy dependence is satisfactorily described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
83
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 6 publications
10
83
0
Order By: Relevance
“…1b. It became clear that such a model grossly underestimates the empirical cross section 3,4]. On the other hand, the predicted energy dependence, which in this model is determined essentially by phase-space factors and the pp nal-state interaction 1], was found to be in agreement with the IUCF data.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…1b. It became clear that such a model grossly underestimates the empirical cross section 3,4]. On the other hand, the predicted energy dependence, which in this model is determined essentially by phase-space factors and the pp nal-state interaction 1], was found to be in agreement with the IUCF data.…”
Section: Introductionsupporting
confidence: 75%
“…pp 0 close to pion production threshold from the Indiana University Cyclotron Facility (IUCF) 1,2] continue to attract the attention of theorists. Early theoretical studies 3,4] followed closely the conventional approach to s-wave meson production which goes back to the work of Koltun and Reitan from 1966 5]. In this model two production mechanisms are considered: (i) direct production of a pion, depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…When data for the reaction pp → ppπ 0 close to threshold became available [2] eq. 1 indeed turned out to give the correct energy dependence of the total cross-section [3]. Several authors [4][5][6][7][8][9] concluded from this observation that it is appropriate to calculate the transition NN → NNx to lowest order in perturbation theory and just include the final state interaction (FSI) by using a formula of the type in eq.…”
mentioning
confidence: 99%
“…This reaction has been addressed in dierent w orks [1,2] and shown to be in strong disagreement with very precise data obtained at the Indiana Cyclotron [3]. The starting point is a model which contains the impulse approximation, diagram 1a) and the rescattering term, diagram 1b).…”
mentioning
confidence: 99%
“…The second one involves the N scattering amplitude in one of the vertices which i s g i v en in terms of an eective Lagrangian Hence only the 1 term contributes, which gives a small contribution given the smallness of 1 . Actually 1 is strictly zero in the limit of exact chiral symmetry.…”
mentioning
confidence: 99%